IINFLUENCE OF PRIOR ANNEALING ON THE LEVEL OF THERMAL STRENGTHENING OF FORGED PIECES OF ALLOY BT23, PRODUCED OF (α+β)AND β-FIELD - V. N. Fedulov (Литьë и металлургия)
It is shown that annealing at 860 ºс increases the size of elements of primary a-phase of alloy BT23, at 950 ºс results in small increase of sizes of b-grains and a-fringe and partial changing of intragrained structure of alloy BT23.